THE IMPACT OF ARABIC LANGUAGE LEARNING MODULES ON STUDENT LEARNING OUTCOMES AT CENDIKIA BATU MUSLIM ELEMENTARY SCHOOL - Shofura, Syifa; Al-latifatuzzahra, Siti Safira; Amalia, Jessica Noer; Daroini, Slamet (Abjadia : International Journal of Education, 2024)
Learning Arabic at Cendikia Batu Muslim Elementary School uses textbooks interestingly enough, the books used belong to the foundation itself. This matter It is proven that the books used make children enthusiastic about learning and grades they exceed the minimum completeness criteria, so this research aims to determine the effect of using Arabic language learning modules on results students studying at Cendikia Batu Muslim Elementary School. This research uses quantitative research with a correlation method Simple Random Sampling technique. Sample In this study there were 29 fifth grade students at Cendikia Muslim Elementary School. With research instruments are questionnaires and documentation. Based on the results of data analysis using the product moment correlation test with significance level of 5% which shows that the rcount value is 0.379 > rtable 0.344 with the level of correlation is weak and there is no negative sign (-) in the rcount with calculations the coefficient of determination is 14.4%. Thus, Ha is accepted and Ho is rejected. So it can be concluded that there is a positive and significant relationship with variable use of Arabic language learning modules on class student learning outcomes V SD Muslim Cendikia Batu.